Evaluating the relationship of body mass index and waist circumference on the image quality of abdominal computed radiography - Abdul Aziz Ismail; Nur Shakila Othman; Mazlyfarina Mohamad; Rozilawati Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2020)
Body sizes of patients undergoing x-ray examination vary in body mass index (BMI) and waist circumference (WC). This study aimed to evaluate the relationship between BMI and WC on the image quality of abdominal computed radiography (CR). Anteroposterior supine abdomen projection was conducted on 69 patients from Hospital Raja Perempuan Bainun, Ipoh using a Siemens Multixtop general x-ray unit, and the images were processed with CR Carestream Direct view Max. Samples were categorised into normal BMI (n = 23), overweight (n = 23) and obese (n = 23). Image quality was measured quantitatively in signal-to-noise ratio (SNR) and qualitatively by visual grading analysis (VGA) based on the Commission of the European Communities (CEC) image criteria. Data were analysed by analysis of variance (ANOVA) and Pearson’s correlation for comparison and determining the relationship among BMI, WC and image quality. Results showed a significant difference (p < 0.01) in image quality of VGAmean (normal = 4.40 ± 0.15, overweight = 4.35 ± 0.13, obese = 4.03 ± 0.34) and SNRmean (normal = 60.79 ± 2.19, overweight = 59.66 ± 1.68, obese = 55.78 ± 4.31). A moderate to high negative correlation existed between SNR (r = −0.73), VGA (r = −0.7) with BMI (p < 0.01) and between SNR (r = −0.83), VGA (r = −0.79) with WC (p < 0.01). This study suggests that WC has a higher negative linear relationship than BMI and can be used as an effective image quality predictor for abdominal CR examination.